Injunctions against false advertising - Florian Baumann; Alexander Rasch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We consider a situation of duopolistic competition in which one firm may (falsely) advertise high product quality. Consumers are heterogeneous. One group forms rational beliefs about quality, whereas some consumers are naive and fully trust any advertisement. We compare two scenarios in which either the competitor or a government agency can file an injunction suit. From a welfare perspective, we show that it may be optimal either to have the competitor or the government agency as plaintiff.
Keywords: K41; K42; L13; L15; 330